Influence of anthropogenic disturbances on understory plant diversity of urban forests in Wuhan, Central China - Zhen Li; Zhuo-Wen Zhang; Yong-Jian Wang; Peng-Cheng Wang; Yong-Rong Xu; Zhi-Xiang Zhou (Universiti Kebangsaan Malaysia, 2012)
Relationship between understory plant diversity and anthropogenic disturbances in urban forests of Wuhan City, Central China, was analyzed by diversity analysis and detrended canonical correspondence analysis (DCCA). The results showed that understory species diversity was higher in suburban area than in urban area. From forest center to edge, species diversity of Luojia hill, Shizi hill and Maan hill forests gradually increased, however, that of Hong hill gradually decreased. Anthropogenic disturbances gradient resulted from visitors flowrate, shrub coverage, aspect and adjacent land types had significant effects on species diversity of shrub and herb layers in urban forests. High anthropogenic disturbances might increase similar non-native herb species in urban area and low disturbances might promote co-existence of wood species in suburban area. Further analysis on types of anthropogenic disturbances and plant functional groups in urban-suburban gradient should be taken into a consideration.